Photoelectrochemical complexes for solar energy conversion that chemically and autonomously regenerate - Ham, Moon-Ho (2010)
Naturally occurring photosynthetic systems use elaborate pathways of self-repair to limit the impact of photo-damage. Herein, we demonstrate a complex that mimics this process consisting of two recombinant proteins, phospholipids and a carbon nanotube. The components self-assemble into a configuration in which an array of lipid bilayers aggregate on the surface of the carbon nanotube, creating a platform for the attachment of light-converting proteins. The system can disassemble upon the addition of a surfactant and reassemble on its removal over an indefinite number of cycles. The assembly is thermodynamically meta-stable and can only transition reversibly if the rate of surfactant removal exceeds about 10(−5) sec(−1). Only in the assembled state do the complexes exhibit photoelectrochemical activity. We demonstrate a regeneration cycle that uses surfactant to switch between assembled and disassembled states, resulting in increased photo-conversion efficiency of more than 300% over 168 hours and an indefinite extension of the system's lifetime.